1993
DOI: 10.1007/bf00167134
|View full text |Cite
|
Sign up to set email alerts
|

High yield fermentation and purification of Tendamistat disulphide analogues secreted by Streptomyces lividans

Abstract: In our studies of structure-function correlation of polypeptides we used Tendamistat (TM), an alpha-amylase-inhibitor of Streptomyces tendae, as a model to investigate the influence of different mutants on the expression and secretion of the protein. In addition, we examined the influence of replacing the two disulphide-bridges that stabilize the two-loop structure of the whole protein. The single mutants C27S, C27T, C45A, the double mutants C11A/C27A, C11A/C27S, C11A/C27T, C11A/C27L, C45/C73A and the fourfold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The disulfide-deficient mutants were constructed as described (Haas-Lauterbach et al, 1993). Protein concentration was determined by UV absorption measurements using an absorption coefficient of A 0,1% 1 cm = 1.61 (Vertesy et al, 1984).…”
Section: Methodsmentioning
confidence: 99%
“…The disulfide-deficient mutants were constructed as described (Haas-Lauterbach et al, 1993). Protein concentration was determined by UV absorption measurements using an absorption coefficient of A 0,1% 1 cm = 1.61 (Vertesy et al, 1984).…”
Section: Methodsmentioning
confidence: 99%
“…The fuzzy halo observed upon interaction with [R19L]Tendamistat indicated that the mutant shows a different behavior, when compared to wild-type Tendamistat. In the preparative isolation by fermentation [16], the yields of [R19L]Tendamistat were in the range 0.5 gA.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The detailed cloning and purification procedure has been published elsewhere. 27 For the 15 N isotope labeling of TM C45A/C73A, the Streptomyces media was prepared as follows: minimal medium (for 50 ml), 12.5 ml 20% (w/v) glucose, 0.5 ml 20% (w/v) ( 15 NH 4 )SO 4 , 5 ml 300 mM sodium potassium phosphate buffer, 1.5 ml 1 M MgSO 4 , 50 µl trace element solution, 0.7-0.75 g Escherichia coliamino acid hydrolysate, prepared in the manner described below. The volume was adjusted to 50 ml with sterile distilled water.…”
Section: Materials and Methods Protein Expression And Purification Prmentioning
confidence: 99%
“…TM C45A/C73A was isolated from culture fluids of Streptomyces lividans and purified according to the procedure reported by Haas-Lauterbach et al 27 Uniform 15 N labeling to a level of 99% was obtained by growing the bacteria in minimal medium containing ( 15 NH 4 )SO 4 and a 15 N-labeled amino acid hydrolysate, obtained by enzymatic hydrolysis of sonified E. coli. Since Streptomyces lividans produces tendamistat only in complex media at a substantial amount, the minimal media have to be supplemented by 15 N-labeled amino acids and proteins.…”
Section: Materials and Methods Protein Expression And Purification Prmentioning
confidence: 99%